2011
DOI: 10.1007/s12094-011-0748-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness evaluation of sunitinib as first-line targeted therapy for metastatic renal cell carcinoma in Spain

Abstract: INTRODUCTION Sunitinib, an oral, multitargeted receptor tyrosine kinase inhibitor, delays disease progression, with a median overall survival (OS) of more than 2 years, improves quality of life and is becoming the first-line standard of care for metastatic renal carcinoma (mRCC). PURPOSE To assess the economic value of sunitinib as fi rst-line therapy in mRCC within the Spanish healthcare system. METHODS An adapted Markov model with a 10-year time horizon was used to analyse the cost effectiveness of sunitinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The present data indicate that it is important for RN pathology to be reviewed by a urological pathologist, as the prognostication of a patient accurately into the intermediate‐ and high‐risk LS prognostic group makes patients eligible for recruitment in clinical trials offering adjuvant treatment. Conversely, patients in whom the prognostic group is changed from intermediate‐ and high‐ to low‐risk not only require a less intense follow‐up schedule but more importantly do not require recruitment into clinical trials that recommend adjuvant treatments, which itself has toxicity related side‐effects and cost‐effectiveness issues . The present study has led to a change of practice at our center, where all nephrectomy specimens are reviewed by uro‐pathologist before a final LS is allocated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data indicate that it is important for RN pathology to be reviewed by a urological pathologist, as the prognostication of a patient accurately into the intermediate‐ and high‐risk LS prognostic group makes patients eligible for recruitment in clinical trials offering adjuvant treatment. Conversely, patients in whom the prognostic group is changed from intermediate‐ and high‐ to low‐risk not only require a less intense follow‐up schedule but more importantly do not require recruitment into clinical trials that recommend adjuvant treatments, which itself has toxicity related side‐effects and cost‐effectiveness issues . The present study has led to a change of practice at our center, where all nephrectomy specimens are reviewed by uro‐pathologist before a final LS is allocated.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who are determined to be at high risk of developing recurrence there continues to be a cohort of patients who have significant side‐effects with adjuvant treatment and are unable to complete the recommended course of treatment . In the current economic climate there are further studies that evaluate the indications and cost effectiveness of commencing tyrosine kinase inhibitors in patients with mRCC .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that sunitinib was cost effective compared with IFN as first‐line mRCC therapy. Similarly, an analysis of the economic value of sunitinib as first‐line mRCC therapy in the Spanish health care system found that sunitinib was a cost‐effective alternative to other targeted therapies, specifically sorafenib and bevacizumab plus IFN .…”
Section: Key Insights In Trial Design and Data Interpretation For Sunmentioning
confidence: 99%